2016
DOI: 10.1093/aje/kww071
|View full text |Cite
|
Sign up to set email alerts
|

A GPS-Based Methodology to Analyze Environment-Health Associations at the Trip Level: Case-Crossover Analyses of Built Environments and Walking

Abstract: Environmental health studies have examined associations between context and health with individuals as statistical units. However, investigators have been unable to investigate momentary exposures, and such studies are often vulnerable to confounding from, for example, individual-level preferences. We present a Global Positioning System (GPS)-based methodology for segmenting individuals' observation periods into visits to places and trips, enabling novel life-segment investigations and case-crossover analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 32 publications
0
66
2
3
Order By: Relevance
“…Using a methodology similar to the one described in our study, these researchers measured NDVI levels at 30-second epochs and found a 34% increased odds of momentary moderate-vigorous physical activity (95% CI 1.30, 1.38) for a 0.11 increase in NDVI. As part of the Residential Environment and Coronary Heart Disease (RECORD) GPS Study, Chaix et al gathered seven days of GPS and accelerometry data on 227 participants in Paris (41). Analyses demonstrated that the probability of walking during a trip was 16% higher (95% CI 2%, 28%) when the trip originated in the top quartile of green space density and 20% higher (95% CI 7%, 33%) when the trip ended in the top quartile of green space density versus the bottom quartile.…”
Section: Discussionmentioning
confidence: 99%
“…Using a methodology similar to the one described in our study, these researchers measured NDVI levels at 30-second epochs and found a 34% increased odds of momentary moderate-vigorous physical activity (95% CI 1.30, 1.38) for a 0.11 increase in NDVI. As part of the Residential Environment and Coronary Heart Disease (RECORD) GPS Study, Chaix et al gathered seven days of GPS and accelerometry data on 227 participants in Paris (41). Analyses demonstrated that the probability of walking during a trip was 16% higher (95% CI 2%, 28%) when the trip originated in the top quartile of green space density and 20% higher (95% CI 7%, 33%) when the trip ended in the top quartile of green space density versus the bottom quartile.…”
Section: Discussionmentioning
confidence: 99%
“…There are a total of 22 studies in children, 17 in youth [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] and 20 in adults. 28, [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] Sample sizes ranged from 12 to 1053; 39% were small (N ≤ 100).…”
Section: Risk Of Bias Appraisalmentioning
confidence: 99%
“…Several studies examined or reported exclusively on time spent in active transportation. [61][62][63][64]74 Commuting/active transportation accounted for between 33% and 68% of total daily MVPA. 61,63,74 Chaix et al 63 found that in general transportation accounted for a median of 13% of ST, but public transportation trips were associated with significantly more ST compared to personalized motor vehicle trips.…”
Section: Location-based Findings For Adults (≥ 18 Years)mentioning
confidence: 99%
“…To the best of our knowledge, there are few previous studies with such extensive datasets. Most studies that focus on GPS measurements included fewer than 300 participants [14,41]. Few larger studies with GPS measurements (Schuessler and Axhausen 2008 N = 4882 and Bohte and Maat 2009 N = 1104) [42,43], did not evaluate characteristics that explain observed differences in mobility patterns.…”
Section: Strengthsmentioning
confidence: 99%